If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 6) = 8x + 2 + -6x + 10 Reorder the terms: 2(6 + x) = 8x + 2 + -6x + 10 (6 * 2 + x * 2) = 8x + 2 + -6x + 10 (12 + 2x) = 8x + 2 + -6x + 10 Reorder the terms: 12 + 2x = 2 + 10 + 8x + -6x Combine like terms: 2 + 10 = 12 12 + 2x = 12 + 8x + -6x Combine like terms: 8x + -6x = 2x 12 + 2x = 12 + 2x Add '-12' to each side of the equation. 12 + -12 + 2x = 12 + -12 + 2x Combine like terms: 12 + -12 = 0 0 + 2x = 12 + -12 + 2x 2x = 12 + -12 + 2x Combine like terms: 12 + -12 = 0 2x = 0 + 2x 2x = 2x Add '-2x' to each side of the equation. 2x + -2x = 2x + -2x Combine like terms: 2x + -2x = 0 0 = 2x + -2x Combine like terms: 2x + -2x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 5x^2-15=4x^2-2x | | 4b-a(3a+6b)-9= | | 0.6(x+300)=0.67x-338 | | 0.3(3z+6)+6.7=0.7(3z-5) | | 2x+6-30-6x=3x+4 | | (7z-a)(3z+2a)= | | 4-(2x-4)=3(3x-7) | | 35/6-5/6:2/3= | | 5x+2y+0.5z=100 | | (-10)+3-24:4-(-5)= | | (4x+12/5)(15t/3x+9) | | 11/18+11/18 | | a+2=2b | | Y=-5x-80 | | -2x+3y=5 | | ln(2x+3)*ln(x^2)=0 | | 7y-2.75=0.5 | | 5*7*11*13= | | (9x-4)=(3x+2) | | y-3=5(x+1) | | (3a-7)(4a+5)= | | y-2=.4(x-3) | | 4y-1.9=6.3 | | 4y-19=6.3 | | m+9=3(m-5)+7 | | -4=3.5-1.5y | | 8m=5m+1 | | 5x+7=-3x-5 | | 4x^4+19x^2-5x+3=0 | | x=8x-50 | | 2(2y-3)=9-2y | | y=.50x-3 |